Informational contagion, the other side of the pandemic (Dimensión Empresarial, 2020)
Along with the current pandemic, there may be an increase in unreasonable behaviors, such as panic purchases or non-compliance with prevention measures. These behaviors are assimilated to contagion from the fake news. To analyze how information is transmitted and how it can lead to the appearance of less than optimal actions, different mechanisms in the behavioral sciences were discussed to improve the follow-up of the recommendations. It concludes with recommendations to improve the application of public policies and practices in the population during crises like the current one.